Romania: tomo 70 (1948-49), tomo 71 (1950), tomo 72 (1951), tomo 73 (1952). - Lope Blanch, Juan M.; Alatorre, Antonio (Nueva Revista de Filología Hispánica (NRFH), 1957)
Se reseñó: Romania: tomo 70 (1948-49), tomo 71 (1950), tomo 72 (1951), tomo 73 (1952).